METTL3-m6A-Rubicon axis inhibits autophagy in nonalcoholic fatty liver disease - Peng, Zishan; Gong, Yingying; Wang, Xuejie; He, Weiman; Wu, Liting; Zhang, Luyao; Xiong, Li; Huang, Yanrui; Su, Lei; Shi, Peijie; Cao, Xiaopei; Liu, Rengyun; et al. (Molecular therapy, 2022)
N6-methyladenosine (m6A) mRNA modification plays critical roles in various biological events and is involved in multiple complex diseases. However, the role of m6A modification in autophagy in nonalcoholic fatty liver disease (NAFLD) remains largely unknown. Here, we report that m6A modification was increased in livers of NAFLD mouse models and in free fatty acid (FFA)-treated hepatocytes, and the abnormal m6A modification was attributed to the upregulation of methyltransferase like 3 (METTL3) induced by lipotoxicity. Knockdown of METTL3 promoted hepatic autophagic flux and clearance of lipid droplets (LDs), while overexpression of METTL3 inhibited these processes. Mechanistically, METTL3 directly bound to Rubicon mRNA and mediated the m6A modification, while YTH N6-methyladenosine RNA binding protein 1 (YTHDF1), as a partner of METTL3, interacted with the m6A-marked Rubicon mRNA and promoted its stability. Subsequently, RUBICON inhibited autophagosome-lysosome fusion and further blocked clearance of LDs. Taken together, our results showed a critical role of METTL3 and YTHDF1 in regulating lipid metabolism via the autophagy pathway and provided a novel insight into m6A mRNA methylation in NAFLD. [Display omitted] Peng et al. provide evidence that METTL3-mediated m6A modification regulates hepatic autophagy and lipid metabolism in a YTHDF1-dependent manner in NAFLD. These findings provide a novel insight into m6A mRNA methylation in NAFLD and may open up a path to develop promising strategies in the prevention of this disease.